2020
DOI: 10.1002/2211-5463.13023
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of amyloid beta with humanin and acetylcholinesterase is modulated by ATP

Abstract: Both HN and AChE can bind Aβ in the absence of added ATP. Addition of ATP increases the binding affinity of Aβ to HN but not to AChE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 107 publications
3
17
0
Order By: Relevance
“…Earlier, we showed that immunodepletion of the neuroprotective peptide, humanin, from the media of A549 and H1299 cells increased the relative abundance of oligomer vs. total levels of amyloid beta, a peptide involved in the Alzheimer disease process, and was correlated with diminished cell viability and increased apoptosis [56]. We then found that ATP, thought to reduce misfolding of amyloid beta, strengthened interactions between amyloid beta and humanin [57]. More recently, we showed that higher intact amyloid beta 40/42 levels are present in the media of A549 (p53 wild-type) than in H1299 (p53-null) lung cancer cell media [44].…”
Section: Discussionmentioning
confidence: 86%
“…Earlier, we showed that immunodepletion of the neuroprotective peptide, humanin, from the media of A549 and H1299 cells increased the relative abundance of oligomer vs. total levels of amyloid beta, a peptide involved in the Alzheimer disease process, and was correlated with diminished cell viability and increased apoptosis [56]. We then found that ATP, thought to reduce misfolding of amyloid beta, strengthened interactions between amyloid beta and humanin [57]. More recently, we showed that higher intact amyloid beta 40/42 levels are present in the media of A549 (p53 wild-type) than in H1299 (p53-null) lung cancer cell media [44].…”
Section: Discussionmentioning
confidence: 86%
“…We also found that the relative abundance of Aβ oligomer versus total Aβ increased upon immunodepletion of the cytoprotective peptide, humanin, from the conditioned media of A549 and H1299 cells, leading to increased apoptosis and diminished cell viability 52 . More recently, we showed that ATP, thought to decrease misfolding of Aβ, strengthened interactions between humanin and Aβ but weakened those between Aβ and acetylcholinesterase 53 . More humanin was bound to Aβ upon ATP addition to media from either A549 or H1299 lung cancer cells, while reduced acetylcholinesterase levels were found in a complex with Aβ by ATP addition to A549 cell media 53 .…”
Section: Resultsmentioning
confidence: 95%
“…More recently, we showed that ATP, thought to decrease misfolding of Aβ, strengthened interactions between humanin and Aβ but weakened those between Aβ and acetylcholinesterase 53 . More humanin was bound to Aβ upon ATP addition to media from either A549 or H1299 lung cancer cells, while reduced acetylcholinesterase levels were found in a complex with Aβ by ATP addition to A549 cell media 53 . To better understand the mechanisms regulating the levels of Aβ in the media, A549 and H1299 cells were grown in FBS-supplemented media for 24 h, then incubated in serum-free media overnight.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Amyloid β peptide aggregation has been accelerated by increasing AChE activity which results in neurodegeneration. 24 In view of these observations, it is therefore inferred that, MELIS prevented neurodegeneration and amyloid beta plaques formation in cerebral cortex by inhibiting AChE activity. Further, persistent amount of ACh was also observed in MELIS-treated AD rats due to inhibition of AChE, which improves the neuronal transmission.…”
Section: Discussionmentioning
confidence: 95%